HUBUNGAN LAMA PENGGUNAAN DIAPERS DENGAN KEMAMPUAN TOILET TRAINING PADA ANAK USIA TODDLER DI DUSUN MAMOKENG DESA TULEHU - Silvianovelista R Losoiyo; Sitti R Latuamury; Harianti Ode (Pasapua Health Journal, 2022)
Introduction: Toddlers are children aged 1-3 years. Toddler growth is characterized by increased locomotion skills, the ability to undress and the development of sphincter control which allows children to toilet train. The use of diapers in the long term and used all the time can have harmful effects and can hinder a child’s toilet training ability. Purpose: to analyze the relationship between the duration of diapers use and toilet training skills in toddlers in Mamokeng Hamlet, Tulehu Village Method: Quantitative research with correlative descriptive through cross sectional approach. The population and sample in this study were mothers who had children aged 1-3 years in Mamokeng Hamlet, Tulehu Village with a total of 35 toddlers. Results: The duration of using diapers in toddler aged children in Mamokeng Hamlet, Tulehu Village was mostly in the old category or ≥ 6 months. Toilet Training Ability for Toddler Age Children in Mamokeng Hamlet, Tulehu Village, is categorized as lacking. There is a relationship between the duration of using diapers and toilet training skills in toddlers in Mamokeng Hamlet, Tulehu Village ρ = 0.003 <0.5. Conclusion: There is a relationship between the duration of using diapers and toilet training skills in toddlers in Mamokeng Hamlet, Tulehu Village. Suggestion: These results can be used as material for consideration or alternatives for institutions as well as schools and kindergartens in developing playing methods such as brain exercises that can be applied in village institutions as materials to improve social skills and reduce children’s anxiety.